Palladinized graphene oxide-MOF induced coupling of Volmer and Heyrovsky mechanisms, for the amplification of the electrocatalytic efficiency of hydrogen evolution reaction - Mogwasha D. Makhafola (Nature Portfolio, 2021)
Abstract In this study, a nanocomposite of palladium supported graphene oxide (GO)/metal–organic framework (MOF) was prepared using electroless deposition of Pd on GO followed by impregnation method of Pd@GO and MOF. The prepared materials were characterized with various analytical techniques and their applications as HER electrocatalysts were evaluated using cyclic voltammetry (CV), Tafel plots, and turn over frequencies (TOFs). The HER results showed a radical increment of H2 production in the nanocomposite through the Volmer reaction together with Heyrovsky or Tafel mechanism. This disclosed that the addition of Pd@GO/MOF in the electrolytic system possessed better catalytic characteristics with enhanced current density which may open a new way for hydrogen production and storage via HER.